Den Grædende Dina over Den Skam-skaaren Sichem: En københavnsk selvkastrat anno 1719 - Færch, Christina Holst (Danske Studier, 2011)
In 1719, a melancholic man castrated himself in Copenhagen. This gave occasion to several anonymous mock-heroic poems about the castration. One of these was »The Crying Dina over the Disfigured Sichem« which was attributed to the notorious libeler Hans Nordrup (1681–1750). The essay accounts for the reception of the poem and also aims to show how the poem parodies the panegyric genre. By installing a low subject in a high style the poem violates decorum. The poem thus refuses to accept the rhetorical demand to docere, delectare et movere: The allegory is here not used for any didactic purposes. Instead, the poem insists on being read for aesthetic and erotic reasons.